The story of Christianity. Volume 1, The early church to the reformation - González, Justo L. (New York : HarperCollins, 2010)
Chronicles the history of Christianity from its infancy to its pervasive dominance at the dawn of the Protestant Reformation, and relates the events, characters, and revolutionary ideas of the religion in its early centuries.
Pt. 1. The early church -- The fullness of time -- The church in Jerusalem -- Mission to the Gentiles -- First conflicts with the state -- Persecution in the second century -- The defense of the faith -- The deposit of the faith -- The teachers of the church -- Persecution in the third century -- Christian life -- The great persecution and the final victory -- Pt. II. The imperial church -- Constantine -- Official theology : Eusebius of Caesarea -- The monastic reaction -- The schismatic reaction : Donatism -- The Arian controversy and the Council of Nicea -- The pagan reaction : Julian the Apostate -- Athanasius of Alexandria -- The great Cappadocians -- Ambrose of Milan -- John Chrysostom -- Jerome -- Augustine of Hippo -- Beyond the borders of the empire -- The end of an era -- Pt. III. Medieval Christianity -- The new order -- Eastern Christianity -- Imperial restoration and continuing decay -- Movements of renewal -- The offensive against Islam -- The golden age of medieval Christianity -- The collapse -- In quest of reformation -- Renaissance and humanism -- Pt. IV. The beginnings of colonial Christianity -- Spain and the new world -- The Portuguese enterprise.
Includes bibliographical references and index.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Church history -- Middle Ages, 600-1500.; Church history -- 30-600, Early church; Church history -- 600-1500, Middle Ages